Service Quality, Institutional Image and Satisfaction : Can Drivers Student Loyalty? - Wijaya, Evelyn; Junaedi, Achmad Tavip; Hocky, Agus (APMBA (Asia Pacific Management and Business Application), 2021)
Education is dynamic and always developing to keep it up to date with today's condition. The government always puts an effort so that the education quality in Indonesia will not be left behind compared to other countries in the world. One of the aspects stimulating the changes is customer demand over the quality of the education system. This study also aimed at analyzing the influence of service quality on the satisfaction and loyalty of senior high school or SMA students. The data used in this study were primary data with a total respondent of 88 students. The technique for data analysis used in this study was path analysis assisted by Smart PLS. The research findings showed that service quality and institutional image significantly influenced satisfaction, yet they did not influence loyalty significantly. Meanwhile, satisfaction directly influenced loyalty. Further study is suggested to add several variables, such as perceived value, perceived quality, and the like that are considered giving an influence on creating student’s loyalty. Practical implications also drawn to conclude this study.